Feasibility of fast, four-dimensional computed tomography-based O-ring LINAC plans for lung stereotactic body radiotherapy in patients with poor performance status - Heo, Eun Jeong; Kim, Minseok; Park, Chun Gun; Chang, Kyung Hwan; Kim, Kwang Hyeon; Shim, Jang Bo; Park, Young Je; Kim, Chul Yong; Lee, Nam Kwon; Lee, Suk (Frontiers in Oncology, 2023)
We aimed to retrospectively analyzed the feasibility of fast four-dimensional computed tomography (4DCT)-based O-ring LINAC treatment for patients with an average respiratory amplitude was < 0.5 cm and who cannot endure long treatment times due to poor performance status in lung 4D-stereotactic body radiotherapy (SBRT).Methods: This study included data of 38 patients who received lung 4D-SBRT and had average respiratory amplitude < 0.5 cm in the full phase. C-arm LINAC plans were based on 4DCT data obtained at phase values ranging from 20-70% using a C-arm LINAC. O-ring LINAC plans were retrospectively established based on 4DCT data obtained at phase values of 0-90% using an O-ring LINAC. The conformity index (CI), homogeneity index (HI), and gradient measurement of the planning target volumes (PTV) were analyzed to compare dosimetric data between C-arm LINAC and O-ring LINAC plans. Organs at risk were analyzed in accordance with the Radiation Therapy Oncology Group 0915 protocol. Treatment delivery time and total monitor units were analyzed to compare the efficiency of treatment delivery.Statistical comparisons were performed using the Wilcoxon signed-rank test (P < 0.05).Results: For the PTV, there was no significant difference in the CI or HI between C-arm LINAC and O-ring LINAC plans. For organs-at-risk, all plans met the criteria for dose constraint. There was a significant difference between C-arm LINAC and O-ring LINAC plans except in the spinal cord. Treatment delivery time was 92% longer for C-arm LINAC plans than for O-ring LINAC plans. The total MU value for C-arm LINAC plans was 9.6% higher than that for O-ring LINAC plans.We verified the feasibility of fast 4DCT-based O-ring LINAC treatment for patients with average respiratory amplitude < 0.5 cm and who cannot endure long treatment times due to poor performance status in lung 4D-SBRT.